A Self‐Assembling Flavin for Visible Photooxidation. Issue 49 (12th July 2022) - Cariello, Michele; Dietrich, Bart; Thomson, Lisa; Gauci, Valentina; Boyer, Alistair; Sproules, Stephen; Cooke, Graeme; Seddon, Annela; Adams, Dave J.
Abstract: A new flavin‐based gelator is reported which forms micellar structures at high pH and gels at low pH. This flavin can be used for the photooxidation of thiols under visible light, with the catalytic efficiency being linked to the self‐assembled structures present. Abstract : The different micellar and gel states formed by a flavin‐based gelator can be used as effective and selective photocatalysts under visible light. The self‐assembled structure formed directly translates into a difference in the activity of these structures in the photooxidation reactions.